Safety and immunogenicity of a recombinant Plasmodium falciparum AMA1-DiCo malaria vaccine adjuvanted with GLA-SE or Alhydrogel® in European and African adults: A phase 1a/1b, randomized, double-blind multi-centre trial. Issue 45 (27th October 2017) - ,; Ouedraogo, E.; Sanou, G.; Gueguen, S.; Lopez Perez, E.; Ammour, K.; Kocken, C.; Batteux, F.; Tartour, E.; Sirima, S.B.; Durier, C.; Kara, L.; et al.
Abstract: Background: Plasmodium falciparum Apical Membrane Antigen 1 Diversity Covering ( Pf AMA1-DiCo) candidate vaccine is a formulation of three recombinant variants of AMA1 designed to provide broader protection against parasites with varying AMA1 sequences. Methods: In this staggered phase Ia/Ib randomized, double blind trial, healthy French adults received AMA1-DiCo with either Alhydrogel® (n = 15) or GLA-SE (n = 15). Following a safety assessment in French volunteers, GLA-SE was chosen for the phase Ib trial where healthy Burkinabe adults received either AMA1-DiCo/GLA-SE (n = 18) or placebo (n = 18). AMA1-DiCo (50 µg) was administered intramuscularly at baseline, Week 4 and 26. Results: AMAI-DiCo was safe, well tolerated either with Alhydrogel® or GLA-SE. In European volunteers, the ratios of IgG increase from baseline were about 100 fold in Alhydrogel® group and 200–300 fold in GLA-SE group for the three antigens. In African volunteers, immunization resulted in IgG levels exceeding those observed for the European volunteers with a 4-fold increase. DiCo-specific IgG remained higher 26 weeks after the third immunization than at baseline in both European and African volunteers. Induced antibodies were reactive against whole parasite derived from different strains. Conclusion: AMA1-DiCo vaccine was safe and immunogenic whatever the adjuvant although GLA-SE appeared more potent than Alhydrogel® at inducing IgG responses. Clinical Trials Registration. ClinicalTrials.gov NCT02014727; PACTR201402000719423.